Ragweed and sagebrush pollen can distinguish between vegetation types at broad spatial scales. Issue 5 (1st May 2020) - Carroll, Hannah M.; Wanamaker, Alan D.; Clark, Lynn G.; Wilsey, Brian J.
Abstract: Patterns of vegetation distribution at regional to subcontinental scales can inform understanding of climate. Delineating ecoregion boundaries over geologic time is complicated by the difficulty of distinguishing between prairie types at broad spatial scales using the pollen record. Pollen ratios are sometimes employed to distinguish between vegetation types, although their applicability is often limited to a geographic range. The Neotoma Paleoecology Database offers an unparalleled opportunity to synthesize a large number of pollen datasets. Ambrosia (ragweed) is a genus of mesic‐adapted species sensitive to summer moisture. Artemisia (sagebrush, wormwood, mugwort) is a genus of dry‐mesic‐adapted species resilient to drought. The log pollen ratio between these two common taxa was calculated across the North American midcontinent from surface pollen samples housed in the Neotoma Paleoecology Database. The relative proportion of Ambrosia has roughly doubled since European settlement, likely due to widespread disturbance, while Artemisia proportions are nearly unchanged. Correcting surface samples for the disturbance signal in modern Ambrosia proportions will allow Ambrosia, a strong indicator of summer moisture, to be more accurately represented. In surface samples where both Ambrosia and Artemisia are reported as nonzero proportions of the pollen sum, mean annual precipitation explains approximately 78% of the variation in the log Ambrosia ‐to‐ Artemisia ratio. Application of this model to Little Ice Age pollen samples produces precipitation reconstructions which generally agree with reconstructions from independent non‐pollen proxies. In addition, we find that modern ecoregions within the North American midcontinent can be successfully distinguished from one another using the log Ambrosia ‐to‐ Artemisia ratio. These relationships can improve reconstructions of past climate and improve delineation of past ecoregion boundaries.